2006
DOI: 10.1007/s10350-006-0684-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Argon Plasma Ablation Therapy for Bleeding in 100 Consecutive Patients with Colonic Angiodysplasia

Abstract: Endoscopic argon plasma ablation therapy is useful in the management of bleeding from colonic angiodysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 36 publications
4
57
1
3
Order By: Relevance
“…In the present study, the mean age of patients with bleeding colonic AGD was 84 years, which is older than that observed in previous studies [7]. In addition, all patients had chronic heart disease, including chronic heart failure, atrial fibrillation, and coronary artery disease or a post-aortic valve replacement or post-mitral valve replacement status.…”
Section: Discussioncontrasting
confidence: 52%
“…In the present study, the mean age of patients with bleeding colonic AGD was 84 years, which is older than that observed in previous studies [7]. In addition, all patients had chronic heart disease, including chronic heart failure, atrial fibrillation, and coronary artery disease or a post-aortic valve replacement or post-mitral valve replacement status.…”
Section: Discussioncontrasting
confidence: 52%
“…It can be directed to specific pathologic mucosa and can cover an expanded area in paintbrush-like fashion. Olmos et al [13] reported a bleed-free period of 2 years for up to 90% of patients after using APC for angiodysplasia. Energy targeting and dosimetry, however, are entirely operator controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Bizim vakamızın APC yöntemiyle beraber destek tedavisine verdiği hızlı cevap APC'nin HHT'ye bağlı anjiodisplazik lezyonlarda seçkin tedavi yöntemi olduğu görüşünü desteklemektedir (22)(23)(24). Yapılan yayınları incelediğimizde HHT'li olgularda özellikle endoskopik ve farmakolojik tedavi kombinasyonun uygulandığı prospektif bir çalışmanın olmaması bu alandaki bilgilerimizi sınırlamaktadır.…”
Section: Discussionunclassified